Combining life and death in Surat Al-Baqarah (Journal of Human Sciences, 2020)
This research studies the phenomena of life and death in the Holy Qur'an. After the initial induction in this topic by following the verses in the entire Qur'an, the researcher discovered the enormity of the topic and the difficulty of studying it in terms of surveying the verses as well as collecting and labelling them. Hence, the researcher decided to prepare an analytical study in the field of Qur'an interpretation by following the verses that brought together the two topics of life and death. Surat Al-Baqarah was chosen as a model for this study because it contained the highest  number of verses that combined the two topics, and after making comparisons and views, the research was decided to be done under the title ( Combining life and death in Surat Al Baqarah). The scope of the study will be confined to the concept of life and death, clarifying their meanings and mentioning some of the famous scholars sayings in this regard and to clarify the aspects of both life and death, to show that  the two are  contradictory  to  each other, and then to display the verses in which life and death were mentioned together in Surat Al-Baqarah. In addition to introducing  Surat Al-Baqarah, mentioning some of its purposes and characteristics and presenting the results of its virtues. After this comes the conclusion, which includes the most important results and recommendations. The conclusion is followed by indexes of sources and references and a table of contents.